LOSING THEIR "MOJO"?: Mobile journalism and the deprofessionalization of television news work. (16th November 2016) - Blankenship, Justin C.
Abstract : Mobile journalism, whereby a single reporter must write, shoot, and edit their own news stories, is a rapidly growing trend among local television news organizations in the United States and around the world. Using qualitative case study methodology, specifically in-depth interviews and observation, this study compares "mobile journalists" with journalists working within a traditional television news crew, in which a reporter concentrates on the writing and interviewing aspects of newsgathering and a videographer concentrates on the audio/video production. The research looked at four aspects of "professionalization" found in the sociology of professions literature; expert knowledge, professional autonomy, routinization, and encroachment from outside organizations. Findings suggest that the mobile journalists in this study have less specialized expert knowledge. Also, though the mobile journalists felt that working outside a crew gave them greater autonomy, their increased use of work routines suggests they have given up some control to organizational needs. Additionally, there is evidence that these mobile journalists have allowed some encroachment by other professionals, specifically public relations professionals, in order to accomplish their work tasks within specified deadlines with limited time and resources.